C# Data Structures and Algorithms Explore the possibilities of C# for developing a variety of efficient applications. - Jamro, Marcin (Packt Publishing, 2018)
Data structures allow organizing data efficiently. Their suitable implementation can provide a complete solution that acts like reusable code. In this book, you will learn how to use various data structures while developing in the C# language as well as how to implement some of the most common algorithms used with such data structures.